EFFECTIVENESS OF TUKUOYUK PLATFORM IN THE GROWTH OF MSMES IN SIDOARJO - Aulia, Firza Farizan; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The results of this study indicate that, to analyse the effectiveness of the TukuoYuk platform in the growth of MSMEs in Sidoarjo. Method: This type of research is qualitative descriptive research, using purposive sampling to select informants. Data collection techniques include interviews, observation, and documentation. The focus of this research is to analyse the effectiveness of the TukuoYuk Platform programme. The data analysis technique used is the interactive data analysis model from Miles & Huberman. Results: The results of this study show that: First, programme understanding, the TukuoYuk Platform has created significant transformative change by increasing the number of MSMEs with planned digital marketing strategies from 18% to 65%. Second, accuracy of target, the TukuoYuk Platform is highly accurate in its targeting, successfully reaching 70% of MSMEs that have never sold online. Third, timeliness, the implementation of the TukuoYuk Platform demonstrates good timeliness, exceeding expectations in achieving its targets. Fourth, achievement of objectives, the TukuoYuk Platform has successfully achieved its main objective by increasing the average turnover of MSMEs by 40%. Fifth, tangible change. The TukuoYuk Platform has created significant transformative change by increasing the number of SMEs with planned digital marketing strategies from 18% to 65%. This is evidenced by increased sales turnover, expanded market reach beyond Sidoarjo, and the creation of new jobs within a year. Novelty: In identifying local digital platform models capable of generating transformative impacts on traditional MSME ecosystems without dependence on national marketplaces, this is evidenced by changes in the business patterns of active merchants who now have planned digital marketing strategies compared to only 18% previously. This study also reveals the phenomenon of collaboration between MSMEs facilitated through local digital platforms, through the TukuoYuk network, which creates a symbiotic business ecosystem model on a local scale but with regional impact.